The Effects Of Sandblasting On The Shear Bond Strenghts Of Used Orthodontic Brackets: An Ex Vivo Study - Selim Arıcı; Tamer Türk; Mete Özer (Galenos Yayinevi, 1999)
The aim of this in vitro study was to determine the effects of sandblasting on the shear bond strengths of the rebonded metal (one mesh-based, one milled-based) and ceramic (one chemically-bonded, one mechanically / chemically-bonded) orthodontic brackets when compared their original bond strengths. The bond failure sites were also investigated. 120 human premolar teeth were randomly assigned to 4 groups of 30 teeth each. Four types of new brackets were bonded with a conventional no-mix composite resin onto teeth, and the original shear bond strengths were tested. These tested brackets were sandblasted with a Microetcher sandblaster until all the composite resin was removed from the bracket base. Then, the sandblasted bracket was rebonded onto the same tooth and the shear bond strengths were tested again. Comparison of the original and rebonded shear bond strengths showed that the ceramic brackets had significantly lower mean shear bond strengths than when they were originally bonded. However, shear bond strengths of the metal brackets were not significanltly effected with sandblasting. Before sandblasting bond failure sites were dominantly at the composite/enamel interface. The predominant bond failure sites, particularly for the ceramic brackets, were at the bracket/composite interface after sandblasting.